Multicentric carpotarsal osteolysis syndrome is caused by only a few domain‐specific mutations in MAFB, a negative regulator of RANKL‐induced osteoclastogenesis. Issue 9 (2nd July 2014) - Mumm, Steven; Huskey, Margaret; Duan, Shenghui; Wenkert, Deborah; Madson, Katherine L.; Gottesman, Gary S.; Nenninger, Angela R.; Laxer, Ronald M.; McAlister, William H.; Whyte, Michael P.
<x xml:space="preserve">Abstract</x> Multicentric carpotarsal osteolysis syndrome (MCTO), an autosomal dominant disorder that often presents sporadically, features carpal–tarsal lysis frequently followed by nephropathy and renal failure. In 2012, mutations in the single‐exon gene MAFB were reported in 13 probands with MCTO. MAFB is a negative regulator of RANKL‐mediated osteoclastogenesis. We studied nine MCTO patients (seven sporadic patients and one affected mother and son) for MAFB mutation. We PCR‐amplified and selectively sequenced the MAFB region that contains the transactivation domain in this 323 amino acid protein, where mutations were previously reported for MCTO. We found five different heterozygous missense defects among eight probands: c.176C > T, p.Pro59Leu; c.185C > T, p.Thr62Ile; c.206C > T, p.Ser69Leu (four had this defect); c.209C > T, p.Ser70Leu; and c.211C > T, p.Pro71Ser. All 5 mutations are within a 13 amino acid stretch of the transactivation domain. Four were identical to the previously reported mutations. Our unique mutation (c.185C > T, p.Thr62Ile) involved the same domain. DNA available from seven parents of the seven sporadic patients did not show their child's MAFB mutation. The affected mother and son had an identical defect. Hence, the mutations for 7/8 probands were suspected to have arisen spontaneously as there was no history of features of MCTO in either parent. Penetrance of MCTO seemed complete. Lack of nonsense or other truncating mutations suggested a dominant‐negative pathogenesis. Our findings indicate that only a few transactivation domain‐specific mutations within MAFB cause MCTO. © 2014 Wiley Periodicals, Inc.